The Paleomagnetism of Kaminak Dikes—No Evidence of Significant Hudsonian Plate Motion - Christie, K. W.; Davidson, A.; Fahrig, W. F. (Canadian Journal of Earth Sciences, 1975)
A paleomagnetic study was done on 28 diabase and 6 lamprophyre dikes from the vicinity of Kaminak Lake in the District of Keewatin. These dikes are Proterozoic and cut across an area of Archean rocks. Their metamorphic grade within this region varies from nil to amphibolite facies. Two stable magnetization directions were obtained from the diabase on AF demagnetization; one from 3 unmetamorphosed diabase dikes of D = 205°, I = 3°, α 95 = 24°, with a corresponding pole position at 23.8 °S, 122.3 °W, α 95 = 16.5°; the other from the metamorphosed diabase of D = 176°,I = 65°, α 95 = 4°, with pole position at 20.4 °N, 92.1 °W, = 6.1°. The first is believed to be thermoremanent and approximately 2300 Ma old, while the second is a metamorphic direction of approximately 1800 Ma. The six lamprophyres give a stable remanence of D = 174°, I = 78°, α 9S = 10°, with a pole position at 40.9 °N, 92.8 °W, α 95 = 17°, essentially the same as the metamorphosed diabase.A number of samples were also thermally demagnetized. Most of the results obtained were the same as those obtained from the AF treatment. However, one diabase site gave a direction similar to that obtained from the 3 unaltered dikes, and one of the lamprophyres showed a reversal.The pole position of the altered Kaminak diabase relative to that for the unconformably overlying Dubawnt Group suggests that the polar wandering curve for this part of the Aphebian may be more complex than previously thought. It is quite probable that the earlier Aphebian pole positions (Matachewan, Nipissing), as usually plotted, are actually antipodal points in terms of the polar wandering curve.